Phototransduction: shedding light on translocation. - Hardie, R.C. (Current Biology, 2003)
Light induces the migration of arrestin to the photosensitive membrane in both vertebrate and invertebrate photoreceptors. New work has identified a phosphoinositide lipid binding domain in Drosophila arrestin and implicates PIP(3) in control of arrestin translocation.